CoQ10 deficiencies and MNGIE: Two treatable mitochondrial disorders - Hirano, Michio; Garone, Caterina; Quinzii, Catarina M. (Biochimica et biophysica acta, 2012)
Although causative mutations have been identified for numerous mitochondrial disorders, few disease-modifying treatments are available. Two examples of treatable mitochondrial disorders are coenzyme Q10 (CoQ10 or ubiquinone) deficiency and mitochondrial neurogastrointestinal encephalomyopathy (MNGIE). Here, we describe clinical and molecular features of CoQ10 deficiencies and MNGIE and explain how understanding their pathomechanisms have led to rationale therapies. Primary CoQ10 deficiencies, due to mutations in genes required for ubiquinone biosynthesis, and secondary deficiencies, caused by genetic defects not directly related to CoQ10 biosynthesis, often improve with CoQ10 supplementation. In vitro and in vivo studies of CoQ10 deficiencies have revealed biochemical alterations that may account for phenotypic differences among patients and variable responses to therapy. In contrast to the heterogeneous CoQ10 deficiencies, MNGIE is a single autosomal recessive disease due to mutations in the TYMP gene encoding thymidine phosphorylase (TP). In MNGIE, loss of TP activity causes toxic accumulations of the nucleosides thymidine and deoxyuridine that are incorporated by the mitochondrial pyrimidine salvage pathway and cause deoxynucleoside triphosphate pool imbalances, which, in turn cause mtDNA instability. Allogeneic hematopoetic stem cell transplantation to restore TP activity and eliminate toxic metabolites is a promising therapy for MNGIE. CoQ10 deficiencies and MNGIE demonstrate the feasibility of treating specific mitochondrial disorders through replacement of deficient metabolites or via elimination of excessive toxic molecules. Studies of CoQ10 deficiencies and MNGIE illustrate how understanding the pathogenic mechanisms of mitochondrial diseases can lead to meaningful therapies. This article is part of a Special Issue entitled: Biochemistry of Mitochondria, Life and Intervention 2010. ►CoQ10 deficiencies can be primary (biosynthetic defects) or secondary (other causes). ►CoQ10 deficiencies often improve with high-dose CoQ10 supplements. ►MNGIE is caused by thymidine phosphorylase deficiency. ►MNGIE can improve after allogeneic hematopoetic stem cell transplantation.